Wear resistance of steels under mechanical wear - M. M. Brikov (Металознавство та обробка металів, 2020)
The potential possibilities of high-carbon low-alloy steels as a wear-resistant material under conditions of abrasive and other types of mechanical wear are considered. It is shown that the carbon content in steel at 1.2% mass. and up to 3% of alloying elements in total (mainly Mn, Cr), after quenching from the single-phase γ-region, allow obtaining up to 100% residual unstable austenite in the structure with a martensite start temperature of about 20 °C. Under conditions of impactless low-cycle wear, when contact stresses exceed the yield strength of the material, plastic deformation and deformation martensitic transformation of austenite occur. This provides high wear resistance that exceeds wear resistance of high-carbon untempered martensite. Adding silicon to steel in an amount of 1.5-2.0% makes it possible after quenching for residual austenite to provide its partial bainitic transformation at a temperature of about 250 °C. Due to the increased silicon content cementite does not form, unconverted austenite is enriched with carbon and stabilizes to a level that provides acceptable impact resistance while maintaining a sufficiently high wear resistance in conditions of low-cycle mechanical wear. Under conditions of multi-cycle wear, plastic deformation and martensitic transformation of unstable austenite do not occur, and its wear resistance is lower than that of quenching martensite. The high wear resistance of high-carbon low-alloy steels under both low-cycle and multi-cycle wear can be achieved by decarburization of the surface layer, for example, during heating under quenching. Due to the low carbon content, the martensitic structure of the surface of hardened steel at a depth of 1 mm will have high wear resistance in conditions of multi-cycle wear. At the same time, the austenitic structure of the core will provide high wear resistance under conditions of low-cycle wear after working out of the surface layer of martensite.